No mesmo barco: a expatriação em aberto e seus impactos na relação conjugal - Santos, Maria Estela Escanhoela Amaral (2017)
The expatriation of employees for an international corporate mission for two to three years could possibly extended if there is an agreement with the parties involving new negotiations and marital reorganization in case of repatriation with accompanying spouses. This descriptive qualitative study of a systemic approach aimed to understand the psychological process underlying expatriation, when this can be left open, considering it as a family project and having as a particular aims: identify the events that produce the mission extension; identify the personal, familiar, marital, environmental and institutional variables that facilitate and hinder initial adjustment and when expatriation can be left open; and understand the experienced process by the couples when the expatriation happens to have no end predicted. It was investigated it through individual face-to-face interviews, six Brazilian expatriates and their respective companionship in European Continent locations. The results showed that difficulties faced in cultural adaptation produced individual and conjugal transformations, favoring the strengthening of the couple, regardless of the lack of clarity in the organizational politics of expatriation. Personal, environmental, institutional, personal network and marital relationship variables were fundamental from the beginning of adaptation until the moment when the expatriation process had become opened, who’s the decision to remain and until when, prioritized projects that became conjugal and familiar throughout the mission